Pengembangan Media Video Pembelajaran Praktikum pada Materi Titrasi Asam Basa Kelas XI SMAN 3 Kupang - Londa, Dorceana; Tukan, Maria B.; Kopon, Aloysius M.; Baunsele, Anselmus Boy (Jurnal Beta Kimia, 2023)
Learning videos are suitable media for various kinds of learning such as in class, small groups and even individual students. By using learning video media, it can clarify the presentation of material, overcome space limitations, overcome students' passive behavior, generate excitement in students, provide the same stimulation and perception, and allow students to learn independently according to their abilities and interests. The purpose of this study was to (1) find out the validity of the teaching video media for acid-base titration material for class XI SMAN 3 Kupang (2) find out the learning outcomes of class XI students at SMAN 3 Kupang after participating in learning using practical learning video media (3) find out the response class XI students of SMAN 3 Kupang on the learning video media for practicum material on Acid-Base Titration. The benefits of this research are (1) For students this research can make students gain new experiences in learning chemistry using interactive learning video media, especially on acid-base titration material, students become more active in the learning process helping students understand the concepts of acid-base titration by easy (2) For teachers this research can provide an overview of learning that focuses on the activeness of students in class XI, providing alternative teaching materials in teaching acid-base duration material, namely by using media tutorial video.This type of research is research and development. The development model used is the ADDIE model (Analysis, Design, Development Implantation, and Evaluation). The instruments used in this research are learning video media validation sheets, learning achievement test sheets, and response questionnaire sheets. students The data analysis technique used is descriptive analysis. From the analysis of the data, it was obtained (1) The practicum-based learning video media developed by researchers was declared very feasible, very valid (2) Student learning outcomes were declared complete with an average score of 89,23 (3) Student responses in learning using learning video media practicum-based is included in the very good category with a percentage of 90%.